(untitled) (Revista INTEREDU11, 2023)
This paper presents the story of a mother and a father of a first grade student who presents Autism Spectrum Disorder (ASD), and unveils their experiences as a family, in the context of the Covid-19 pandemic and the barriers that prevented them from having an inclusive education for the child. This study is presented and framed in the academic literature referring to educational inclusion and contextualized in the few measures taken by the Chilean State in such matter. In turn, it is presented the conversation and the experience of Judith Cáceres, about her own experiences as a mother of a girl with Type 1 Diabetes Mellitus and her search for inclusive education, a case published in number 7, of 2022, on INTEREDU journal. This essay aims to make visible the difficulties experienced by students with special educational needs (SEN) during the Covid-19 pandemic and calls to reflect on the inclusion of children and adolescents who live under this condition, in the context of the recent approval of Law 21.545, also called TEA Law, in Chile.